2005
DOI: 10.1902/jop.2005.76.11-s.2075
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Model Linking Inflammation to Obesity, Diabetes, and Periodontal Infections

Abstract: Obesity is a significant predictor of periodontal disease and insulin resistance appears to mediate this relationship. Furthermore, obesity is associated with high plasma levels of TNFalpha and its soluble receptors, which in turn may lead to a hyperinflammatory state increasing the risk for periodontal disease and also accounting in part for insulin resistance. Further studies of the molecular basis of insulin resistance and its relationship to diabetes, periodontal disease, and obesity are necessary to fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
538
4
43

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(631 citation statements)
references
References 44 publications
20
538
4
43
Order By: Relevance
“…Nishida et al 27) suggested that obesity was second only to smoking as the predominant risk factor for inflammatory periodontal destruction of tissue. The results of other cross-sectional studies 1,8,15,22,36,37,43) also indicate an association between obesity and periodontal disease. The biological mechanisms for an association between obesity and periodontitis remain to be clarified.…”
Section: Discussionmentioning
confidence: 73%
“…Nishida et al 27) suggested that obesity was second only to smoking as the predominant risk factor for inflammatory periodontal destruction of tissue. The results of other cross-sectional studies 1,8,15,22,36,37,43) also indicate an association between obesity and periodontal disease. The biological mechanisms for an association between obesity and periodontitis remain to be clarified.…”
Section: Discussionmentioning
confidence: 73%
“…Being obese or overweight has been suggested to be associated with periodontitis, because obesity due to inflammatory mediators may affect systemic health through influencing host susceptibility to periodontitis 12) . Periodontitis is a common chronic inflammatory oral disease of the adult population characterized by a gingival inflammatory response to pathogenic bacterial microflora, resulting in alveolar bone loss and eventually tooth loss 29) .…”
Section: Discussionmentioning
confidence: 99%
“…39 TNF-a produced from the adipocytes was shown to be a pathogenic factor linking obesity to diabetes and periodontal disease. 40 These findings indicate that systemic approach for periodontal therapy and prevention are needed in addition to the local control of infection and inflammation. Therefore, we suggest that orally administrated L-bLF may be more effective for the prevention of periodontitis especially in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%